The burden of hyponatremia and 30-day outcomes among adults admitted with stroke at a large tertiary teaching hospital in Northwestern Tanzania - Katanga, Johari; Nkandala, Igembe; Ngimbwa, Joshua; Mwamba, Lilian Andrew; Paul, Innocent Kitandu; Berling, Sospeter; Xavier, Gladness; Basinda, Matilda K.; Kagoye, Sophia; Mahawish, Karim; Matuja, Sarah Shali (Frontiers in Stroke, 2025)
BackgroundThe most frequent electrolyte derangement in adults with stroke is hyponatremia, which is associated with increased morbidity, mortality, and prolonged hospital stay. The study aimed to investigate the hyponatremia incidence and 30-day outcomes among adults admitted with stroke at a large tertiary teaching hospital in Northwestern Tanzania.MethodsThis cohort study recruited adults presenting with first-ever stroke (as defined by the World Health Organization) between November 2023 to May 2024. Data were collected on demographics, the degree of neurological impairment at admission using the National Institutes of Health Stroke Scale (NIHSS), and laboratory workup, including sodium levels, on admission; the modified Rankin Scale was used to assess stroke outcomes. We used modified Poisson and logistic regressions to examine factors associated with hyponatremia and 30-day outcomes, respectively.ResultsIn total, 167 adults were enrolled, of which 56.9% (n = 95) were female, with a median age of 60 years (interquartile range [IQR] 40–74), and 71.2% (n = 119) had hypertension and heart failure. The hyponatremia incidence was 29.3% (n = 49), and among these participants, 53% (n = 26) had mild hyponatremia. Factors associated with hyponatremia were the use of mannitol on admission (adjusted prevalence ratio [aPR] 3.14, 95% CI [1.81, 5.44], p < 0.001) and increasing NIHSS scores (aPR 1.03, 95% CI [1.00, 1.06], p < 0.05). There were no differences in 30-day mortality between those with and without hyponatremia (respectively, 38.3% vs. 36.7%, p = 0.79). The presence of leukocytosis was independently associated with 30-day mortality (adjusted odds ratio [aOR] = 2.7, 95% CI [1.39, 5.36], p = 0.004), and the median length of hospital stay was significantly higher in those with hyponatremia compared to those without: 7 days (IQR 4–9) vs. 5 days (IQR 3–9), p = 0.032.ConclusionHyponatremia, which is associated with increased stroke severity, probable infections, and prolonged hospital stays, is prevalent among adults with stroke in Northwestern Tanzania. The high prevalence of hypertension and heart failure underscores the need for targeted preventive strategies. Early detection and appropriately managing hyponatremia are essential to improve stroke outcomes in this region.